\(a)\)
\(A=\left(m-1\right)^3-\left(m-2\right)^3\)
\(=\left(m^3-3m^2+3m-1\right)-\left(m^3-6m^2+12m-8\right)\)
\(=m^3-3m^2+3m-1-m^3+6m^2-12m+8\)
\(=3m^2-9m+7\)
\(B=\left(3m-1\right)\left(3m+1\right)\)
\(=9m^2-1\)
\(\dfrac{1}{9}A=B-7\)
\(\Rightarrow\dfrac{1}{9}\left(3m^2-9m+7\right)=9m^2-1-7\)
\(\Rightarrow3m^2-9m+7=81m^2-72\)
\(\Rightarrow78m^2+9m-79=0\)
\(\Rightarrow m=\dfrac{-9\pm\sqrt{24729}}{156}\)
\(b)\)
\(A< B\)
\(\Rightarrow3m^2-9m+7< 9m^2-1\)
\(\Rightarrow6m^2+9m-8>0\)
\(\Rightarrow\left[{}\begin{matrix}m>\dfrac{-9+\sqrt{273}}{12}\\m< \dfrac{-9-\sqrt{273}}{12}\end{matrix}\right.\)